10.1016/s1541-9800(10)70214-3 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Many individuals with trichotillomania find themselves unable to access effective treatment and are forced to manage symptoms independently. Support groups play an important role in symptom management. AIMS: This qualitative study aimed to explore experiences with online support groups among hair-pulling individuals (N = 20; 10 women, 7 men, 3 non-binary). METHODS: Data were collected online via semi-structured interviews. Reflexive thematic analysis yielded four themes: (1) group usage, (2) detrimental group effects, (3) group benefits, and (4) attitudes towards groups. RESULTS: A major advantage of online groups over in-person support was the ability for participants to join from home. Participants could join without having to share their appearances, bypassing much of the stigma associated with traditional treatment options. Few participants reported worsening symptoms after joining support groups which they attributed to re-exposure to pulling triggers, but most had positive views of their groups. CONCLUSIONS: Support groups may play a beneficial role in the management of distress in chronic hair-pullers.